FAKTOR RISIKO ASFIKSIA NEONATORUM - Rini Mustikasari Kurnia Pratama; Ayu Mustika Handayani (Jurnal Ilmu Kebidanan, 2022)
Background: Asphyxia neonatorum is the third highest cause of newborn death after neonatal infection and low birth weight infants. Asphyxia is associated with long-term morbidity, namely mental retardation, cerebral palsy and occurrence of learning disorders in infants and child development. Purpose: the purpose of this study was to determine the relationship between gestational age, birth weight of the baby, history of premature rupture of membranes, and hypertension in pregnancy to the incidence of asphyxia neonatorum. Methodes: analytic with a retrospective approach, the total number of newborns with asphyxia neonatorum as a population, as many as 117 respondents with a total sampling. Data analysis using chi-square test. Result: there is a relationship between gestational age (p-value 0.000; OR 4.00), baby’s birth weight (p-value 0.001; OR 2.81), history of premature of membranes (p-value 0.000; OR 3.01), and hypertension in pregnancy (p-value 0.000; OR 2.10) on incidence of asphyxia neonatorum.. Conclusion: there is a significant relationship between gestational age, baby’s birth weight, history of premature rupture of membranes, and hypertension in pregnancy to the incidence of asphyxia neonatorum and these four variables are risk factors for incin=dence of asphyxia neonatorum.